A Nobel Approach of Hybrid Routing Protocol In Mobile Ad-hoc Network - Bano, A; Yadav, R.K; Namdeo, V (International Journal of Computer Sciences and Engineering, 2025)
The goal of MANET is formation of a self-organized and self- configurable network of mobile nodes with wireless connectivity, where the nodes move arbitrarily. Routing is a critical issue in Mobile Adhoc Network. Therefore, Routing protocols for this network have to face the challenge of frequently changing topology. Both proactive and reactive routing protocols prove to be inefficient under these circumstances. Third category, Hybrid routing protocols combines the advantage of Proactive as well as the reactive protocols. This research work is equipped with some goals of analyzing the behaviour of existing MAC protocol over the hybrid type of routing for ad hoc networks, analyzing the impact of delay while receiving the data over the zone based communication (inside/outside of the zones), developing a solution by enhancing the existing MAC protocol and also analyzing the behaviour of the zone routing protocol with proposed algorithm. Hence in this research work calculation of the performance routing protocol using different parameters such as receiving time, bandwidth, packet loss etc obtained